Comparison of blood glucose levels in breastfed vs. formula-fed low birth weight infants - Eli Tua Pangaribuan; Bugis M. Lubis; Pertin Sianturi; Emil Azlin; Guslihan D. Tjipta (Indonesian Pediatric Society, 2009)
Background Low birth weight infants are defined as babies withbirth weight less than 2500 grams. Low birth weight infants tendto suffer from hypoglycemia compared to full term infants. Theincidence of hypoglycemia in newborns varies between 1.3 and 3per 1000 live births. Blood glucose levels in formula-fed infantsare lower than those in breastfed infants.Objective To compare blood glucose levels in breastfed andformula-fed low birth weight infants.Methods A cross sectional study was conducted between February2007 and June 2007 at Pirngadi and H. Adam Malik GeneralHospital in Medan, North Sumatra, Indonesia. All low birthweight babies were classified into two groups: the breastfed andformula-fed. Each group consisted of 32 infants. Capillary bloodwas collected using heel pricks at 1, 48, and 72 hours after birth,and plasma glucose was evaluated using the Glucotrend2 bloodglucose test.Results The breastfed low birth weight infants had significantlyhigher blood glucose levels (P=0.002) than formula-fed low birthweight infants. Mode of delivery was related to blood glucose level.Infant delivered by caesarean section had significantly differentblood glucose levels at 1 hour (P=0.005) and 72 hours afterbirth (P=0.027). The full-term infants had significantly higherblood glucose level (P=0.007) than the small for gestational ageinfants.Conclusions Generally, low birth weight infants have hypoglycemiaafter first hour of delivery. Breastfed low birth weight infants havehigher blood glucose levels than formula-fed low birth weightinfants.